Public Debt and Economic Growth: Case of South American Nations - Chanagul, Chittawan (Journal of Multidisciplinary in Humanities and Social Sciences, 2023)
This paper aimed to study the relationship between public debt and economic growth in South American nations. To achieve the objective, a panel analysis was adopted. The results drawn from this study suggested that mean years of schooling as well as trade openness and investment have a positive impact on growth rates, whereas public debt is negatively related to economic growth. Not surprisingly, the corruption perception index has a positive relationship with growth. In other words, when a nation has a low prevalence of corruption, economic growth increases.